Selisik atas Metodologi Kritik Matan Ulama Hadis - Lalu Heri Afrizal (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2016)
This article assumes most contemporary intellectuals who considered that the scholars of hadith do not concentrate to criticism of “matan” of hadith. According to them, the classic hadith scholars portray not much sense in reviewing and critiquing the prophetic traditions. This criticism is inherited and developed by some reviewers of prophetic tradition in the West. Some may think that the scholars did not use a lot of sense in criticizing the hadith. In fact, any study of any text can not be done without using the sense. But, in studying the hadith texts, the scholars of hadith did not rely on the opinions of the sense only, but they put the sense into its position proportionally. Related to this, the criticism methodology of “sanad” is part of the criticism of “matan” that can not be separated, because of the efforts of the scholars in reviewing “sanad” is to prove the authenticity and validity of “matan”. The validity of a hadith should be assessed through a study of the “sanad” and “matan” once. To judge a hadith by the sense only can not be accepted. So, to prove the truth of any information is not enough just by assumption or opinion of the sense itself. Proving the accuracy of “riwayat” empirically has been done by the previous hadith scholars, and it is their main activity to prove the truth of narration of hadith they heard and understood by their sense.